Bajka w życiu dziecka = A fairy tail in the life of a child - Siemież, Małgorzata B. (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
In this paper the author on a number of fairy tales wonders to what extent they affect the youngest reader. By selecting the appropriate fables and reading them to a child usually a boy or a girl shapes its personality. He/she willingly identifi es himself/herself with fairytale characters, then he/she enters into the role of the main characters for diff erent reasons.
Keywords: bajka; dziecko; rozwój emocjonalny; uważność; story; child; emotional development; mindfulness